PENGARUH PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN PANCASILA DI KELAS III B SD NEGERI 060922 MEDAN SUNGGAL - Pasaribu, Sarmauli; Patri Janson Silaban; Heka Maya Sari Sembiring; Regina Sipayung; Juliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning outcomes of students in Pancasila Education indicate that the learning process has not fully accommodated students' diverse learning needs. This study aimed to determine the effect of differentiated learning on students' learning outcomes in Pancasila Education on the topic “Different is Beautiful” in Class III B of SD Negeri 060922 Medan Sunggal for the 2025/2026 academic year. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest-Posttest Design. The population and sample consisted of 21 students of Class III B. Data were collected through tests and questionnaires. The research instruments were tested for validity and reliability using SPSS version 25. Data analysis techniques included normality testing, product moment correlation, coefficient of determination, and t-test. The results showed that the average pretest score was 52.57, while the average posttest score increased to 83.52 after the implementation of differentiated learning. The correlation coefficient obtained was 0.945, indicating a very strong relationship. The coefficient of determination (R²) was 0.894, meaning that differentiated learning contributed 89.4% to students’ learning outcomes. Furthermore, the t-test results showed that tcount = 12.636 > ttable = 2.093 with a significance value of 0.000 < 0.05. Therefore, the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It can be concluded that differentiated learning has a significant positive effect on students’ learning outcomes in Pancasila Education.